Eksistensi Aspek Modal Pierre Bordieu pada Buruh Gendong Pasar Legi Kota Surakarta - Ika Agustina; Ayu Riyanti; Rani Titis Sukowati (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to explain the forms of capital possessed, maintained, and expanded by Buruh Gendong (female porters) in order to gain economic benefits. Pasar Legi is the traditional market with the largest number of Buruh Gendong in Surakarta, employing approximately 300 workers. This research employs a qualitative method with an ethnographic approach, while the data analysis technique used is an interactive model. The findings indicate that Buruh Gendong possess several forms of capital that support their economic activities. First, social capital includes close ties with traders and membership in the Indonesian Transport Workers Union (SPTI). Second, economic capital consists of their main income from porter work and additional income such as peeling onions. Third, cultural capital is reflected in their ability to negotiate service prices. Fourth, symbolic capital lies in the social status they hold within the market. These capitals are closely tied to the social relations between the Buruh Gendong, traders, and customers when offering their services. Such social relations serve to maintain, expand, and exchange capital within a social arena referred to as the market. However, competition within this arena often results in conflicts among the Buruh Gendong themselves.Penelitian ini bertujuan untuk menjelaskan aspek modal yang dimiliki, dipertahankan, dan diperluas oleh Buruh Gendong untuk memperoleh keuntungan ekonomi. Pasar Legi merupakan pasar yang memiliki jumlah buruh gendong terbesar di Kota Surakarta, sebanyak 300 pekerja. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan etnografi. Sedangkan teknik analisis data yang digunakan adalah analisis data model interaktif. Berdasarkan hasil penelitian, buruh gendong memiliki beberapa aspek modal dalam menunjang aktivitas ekonomi. Pertama, modal sosial yang dimiliki adalah kedekatan khusus dengan pedagang dan tergabung dalam anggota SPTI (Serikat Pekerja Transport Indonesia). Kedua, modal ekonomi yang dimiliki yaitu pendapatan utama (buruh gendong) dan pendapatan sampingan (pengupas bawang). Ketiga, modal budaya yang dimiliki adalah kemampuan negoisasi harga. Keempat, modal simbolik yang dimiliki adalah status sosial buruh gendong di pasar. Aspek modal tersebut, tidak dapat lepas dari relasi sosial antara buruh gendong dengan pedagang dan pelanggan dalam menawarkan jasanya. Relasi sosial yang terjalin untuk mempertahankan, memperluas, dan mempertukarkan aspek modal yang dipertaruhkan dalam ranah yang kita sebut pasar. Pertaruhan dalam ranah sering kali menimbulkan persaingan konflik antar buruh gendong.